2005
DOI: 10.1002/cncr.21303
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome after radiotherapy alone for lymphocyte‐predominant Hodgkin lymphoma

Abstract: BACKGROUNDThe curative potential of radiotherapy (RT) alone as initial treatment for patients with Stage I–II lymphocyte‐predominant Hodgkin lymphoma (LPHL) has not been defined well.METHODSTwo hundred two patients who were treated between 1969 and 1995 were evaluated in a retrospective, multicenter study.RESULTSPatient characteristics were as follows: The median age was 31 years, 75% of patients were male, 80% of patients had Ann Arbor Stage I disease, 1% of patients had bulky disease, 3% of patients had B sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(33 citation statements)
references
References 26 publications
(52 reference statements)
3
29
0
Order By: Relevance
“…6 The risk of progression was reduced with radiotherapy compared to watchful waiting. However, with a 4-year PFS estimate of 79.6% for patients treated with radiotherapy alone, the benefit of radiotherapy is inferior to the results of previously published studies, 8,13,14 and relapses occurred in most cases outside the irradiated fields. Due to the low number of patients and events, a comparison between the results of radiotherapy in stage I and stage II was not possible.…”
Section: Discussionmentioning
confidence: 57%
“…6 The risk of progression was reduced with radiotherapy compared to watchful waiting. However, with a 4-year PFS estimate of 79.6% for patients treated with radiotherapy alone, the benefit of radiotherapy is inferior to the results of previously published studies, 8,13,14 and relapses occurred in most cases outside the irradiated fields. Due to the low number of patients and events, a comparison between the results of radiotherapy in stage I and stage II was not possible.…”
Section: Discussionmentioning
confidence: 57%
“…[19][20][21][24][25][26][27] However, excellent results are also obtained with combined modality therapy, as shown by clinical trials of the German Hodgkin Study Group. 19,26 When RT alone is used, involved field or slightly extended field RT should be adequate (Table 3), without resorting to the use of classical extended field techniques such as the Mantle (Fig 2A and B), or inverted Y fields.…”
Section: Nodular Lymphocyte Predominant Hodgkin's Lymphoma (Nlphl)mentioning
confidence: 88%
“…19,26 When RT alone is used, involved field or slightly extended field RT should be adequate (Table 3), without resorting to the use of classical extended field techniques such as the Mantle (Fig 2A and B), or inverted Y fields. 20,27 Despite very high response rate, relapses are common, characteristically occurring late in follow up, compared with patients with classical HL. However, it appears that patients relapsing with NLPHL has a better outcome compared with other classical HL patients and that death from NLPHL is uncommon.…”
Section: Nodular Lymphocyte Predominant Hodgkin's Lymphoma (Nlphl)mentioning
confidence: 98%
“…Causes of death at 15 years were LPHL in 3% of patients, NHL in 2%, in-field malignancy in 2%, in-field cardiac or respiratory causes in 4%, and other in 6%. The authors demonstrated that radiotherapy may be curative for patients with Stage I or II LPHL and suggested that limited-field radiotherapy might be used without loss of treatment efficacy in this patient group [19].…”
Section: Treatment Of Early-stage Lphl Without Risk Factorsmentioning
confidence: 99%
“…Establishing a standard treatment for LPHL patients in early stages is difficult, however, because of the low incidence of LPHL and the very few events observed in early stages. As a result, treatment of early LPHL is rather heterogeneous, including extendedfield radiotherapy (EF-RT), involved-field radiotherapy (IF-RT), combined-modality (CM) treatment, and, more recently, monoclonal antibodies [6•, 7,8,19,20].…”
Section: Treatment Of Early-stage Lphl Without Risk Factorsmentioning
confidence: 99%